The role of the microcirculation and integrative cardiovascular physiology in the pathogenesis of ICU-acquired weakness - Mendelson, Asher A.; Erickson, Dustin; Villar, Rodrigo (Frontiers in Physiology, 2023)
Skeletal muscle dysfunction after critical illness, defined as ICU-acquired weakness (ICU-AW), is a complex and multifactorial syndrome that contributes significantly to long-term morbidity and reduced quality of life for ICU survivors and caregivers. Historically, research in this field has focused on pathological changes within the muscle itself, without much consideration for their in vivo physiological environment. Skeletal muscle has the widest range of oxygen metabolism of any organ, and regulation of oxygen supply with tissue demand is a fundamental requirement for locomotion and muscle function. During exercise, this process is exquisitely controlled and coordinated by the cardiovascular, respiratory, and autonomic systems, and also within the skeletal muscle microcirculation and mitochondria as the terminal site of oxygen exchange and utilization. This review highlights the potential contribution of the microcirculation and integrative cardiovascular physiology to the pathogenesis of ICU-AW. An overview of skeletal muscle microvascular structure and function is provided, as well as our understanding of microvascular dysfunction during the acute phase of critical illness; whether microvascular dysfunction persists after ICU discharge is currently not known. Molecular mechanisms that regulate crosstalk between endothelial cells and myocytes are discussed, including the role of the microcirculation in skeletal muscle atrophy, oxidative stress, and satellite cell biology. The concept of integrated control of oxygen delivery and utilization during exercise is introduced, with evidence of physiological dysfunction throughout the oxygen delivery pathway – from mouth to mitochondria - causing reduced exercise capacity in patients with chronic disease (e.g. heart failure, COPD). We suggest that objective and perceived weakness after critical illness represents a physiological failure of oxygen supply-demand matching - both globally throughout the body and locally within skeletal muscle. Lastly, we highlight the value of standardized cardiopulmonary exercise testing protocols for evaluating fitness in ICU survivors, and the application of near-infrared spectroscopy for directly measuring skeletal muscle oxygenation, representing potential advancements in ICU-AW research and rehabilitation.